Effect of Mechanism Error on Input Torque of Scroll Compressor - Man Zhao; Shurong Yu; Chao Li; Yang Yu (International Journal of Rotating Machinery)
Based on the fundamental principle of plane four-bar mechanism, the force on the equivalent parallel four-bar mechanism was analyzed for scroll compressor with mini-crank antirotation, and the formula of input torque was proposed. The change of input torque caused by the mechanism size error was analyzed and verified with an example. The calculation results show that the mechanism size error will cause large fluctuation in input torque at the drive rod and connecting rod collinear and the fluctuation extreme value increases with rotational speed. Decreasing of the crankshaft eccentricity errors is helpful for reducing the effects of dimension error on input torque but will increase the friction loss of orbiting and fixed scroll wrap. The influence of size error should be considered in design in order to select suitable machining accuracy and reduce the adverse effect caused by size error.